The Effects of Plyometric and Resistance Training on Explosive Power and Strength of Young Male Volleyball Players - Ramin Aghajani; Zahra Hojjati; Alireza Elmiyeh (The Society of Aging and Physical Activity (SAPA), 2014)
This paper examines the effects of plyometric and resistance training on the explosive power and the amount of young male volleyball players' strength in Guilan province. The participants include 45 volleyball players, 15-22 years old, which were randomly divided into three groups: two training groups and one control group. Among the two training groups, one was engaged in plyometric and the other in resistance exercise training (six weeks, two times per week).The control group was doing its common volleyball training. Variables under measurement consist of strength and explosive power. We found that after a six weeks training, there were significant differences between the average of explosive power and strength in both groups of plyometric and resistance training in comparison to control group (P≤0.05). The researcher observed that there was a significant difference in the average of explosive power and strength within both plyometric and weight groups from pre to post-test (p≤0.05). The amount of improvement in resistance training group was more than plyometric group.